First record of the chimaera Neoharriota carri (Bullis and Carpenter 1966) in the Caribbean of Guatemala. Issue 1 (December 2017) - Polanco-Vásquez, Francisco; Hacohen-Domené, Ana; Méndez, Thalya; Pacay, Alerick; Graham, Rachel
Abstract Background A new record ofNeoharriota carri is here reported for the Caribbean of Guatemala. Results Two chimaeras, a male and femaleNeoharriota carri, were caught with a single panel trammel net off the coast of El Quetzalito, Guatemala in February 2015 and January 2016 respectively. Details concerning the identification and measurement of these species are presented. Conclusions These records represent the first records in Guatemalan waters and the northernmost records in the western Atlantic for the distribution ofN. carri .